2019
DOI: 10.3390/designs3020026
|View full text |Cite
|
Sign up to set email alerts
|

Design of PI Fuzzy Logic Gain Scheduling Load Frequency Control in Two-Area Power Systems

Abstract: In this paper the use of the proportional integral (PI) algorithm incorporated with the fuzzy logic technique has been proposed as advanced gain scheduling load frequency control (GLFC) in two-area power systems. The proposed controller comprises two-level control systems, such that it consists of a pure integral compensator which is connected in parallel with a PI controller. However, and based on load demand, the PI parameters are updated online by means of fuzzy logic rules. With this control technique it b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The performance of the proposed controller has been validated by comparing its results with those of a recently published PID-P controller, where it achieved less settling time and less undershooting and overshooting values. In [28], T. Hussein and A. Shamekh proposed a gain-scheduling PI fuzzy logic two-level LFC for a two-area power system. This technique eliminates steady-state error and results in good transient response.…”
Section: Fuzzy Logic Controlmentioning
confidence: 99%
“…The performance of the proposed controller has been validated by comparing its results with those of a recently published PID-P controller, where it achieved less settling time and less undershooting and overshooting values. In [28], T. Hussein and A. Shamekh proposed a gain-scheduling PI fuzzy logic two-level LFC for a two-area power system. This technique eliminates steady-state error and results in good transient response.…”
Section: Fuzzy Logic Controlmentioning
confidence: 99%
“…This study is extended to a multi-area interconnected power system as demonstrated in Figure 17. This model is extensively investigated in the literature to study the dynamic behavior of different control concepts for LFC in power systems [36,37]. It consists of two unequal thermal interconnected areas; the parameters of this model are tabulated in Appendix C. Based on the function of the LFC loop in multi-area power systems, the main tasks of LFC are providing the required power from the generation units to meet the load variation and maintaining the interchanged power among interconnected control areas via tie-lines at pre-rated values.…”
Section: Load Frequency Control For Dual-area Power Systemmentioning
confidence: 99%
“…So far, many advanced methods for LFC systems have been proposed against different system disturbances. As an example, nonlinear methods such as sliding mode control, 2 model predictive control, 3 internal model control 4 ; heuristic optimization based methods such as artificial bee colony, 5 grey wolf optimization, 6 improved salp swarm optimization 7 ; artificial intelligence based controllers such as fuzzy logic, 8 artificial neural network, 9 generalized hopfield neural network 10 or hybrid control techniques such as hybrid gravitational search and pattern search, 11 hybrid harmony search and cuckoo optimization algorithm 12 can be specified. Furthermore, advanced neural network‐based methods such as artificial emotional reinforcement learning, 13 extreme learning machine, 14 and integral reinforcement learning 15 have also provided significant improvements on LFC performance.…”
Section: Introductionmentioning
confidence: 99%